PROFIL FITOKIMIA DAN PEMERIKSAAN FARMAKOGNOSTIK DAUN ANTING-ANTING (Acalypha indica. L) - Selpida Handayani; Abd. Kadir; Masdiana Masdiana (Jurnal Fitofarmaka Indonesia, 2018)
The Anting-anting (Acalypha indica L.) plant of the tribal Euphorbiaceae is one type of plant commonly used as a medicinal plant. The Purpose of This study is to get the morphology data, anatomy, organoleptic, physical determination of powders, powder ekstrabilitas determination, identification of chemical reactions and thin layer chromatography of Anting-anting (Acalypha indica L.) plant. Extraction of Anting-anting (Acalypha indica L.) leaf is using 96% ethanol by maceration method. Longitudinal slices showed stomata leaf anatomy anisositik type. Fisic desition include 16,36 % decision of dust level 5,16% decision of unsoluble dust in acid level. Decision of cansentrate level that include 25,16% consentrate level of water soluble and 26,36% consentrate level of etanol soluble. The results of this study concluded thet the leaf powder Anting-anting (Acalypha indica L.) is positive for flavanoid, alkaloid, steroid, saponin and aleuron.